Comparative Study DO, CO2,pH in Tanjung Kudu lake Kualu Village Tambang District Kampar Regency and PLTA Koto Panjang Hydroelectric Reservoir Riau Province - Munthe, Ayaki Tomala; Simarmata, Asmika Harnalin; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis research about comparative study DO, CO2, pH in Tanjung Kudu Lake Kualu Village, Kampar Regency and PLTA Koto Panjang Hydroelectric Reservoir Riau Province was conducted on January 2021. There were 3 station in Tanjung Kudu Lake as well as Koto Panjang Hydroelectric Reservoir. Sampling was done every 4 hours during 3 days. Sampling in Tanjung Kudu Lake based on Secchi depth namely surface and 2 Secchi depth and in Koto Panjang Hydroelectric Reservoir, namely surface, 2 Secchi depth, 4 Secchi depth, 10 Secchi depth, 20 Secchi depth, and the bottom of lake. The Result shownthe average of DO in Tanjung Kudu Lake ranges from 4.62–7.53 mg/L, CO2 ranges from 4.00–8.88 mg/L, pH 5, temperatures ranges from 27–30°C, transparency ranges from 34-49 cm, depth ranges from 1,2-2 m, and in Koto Panjang Hydroelectric Reservoir concentration of DO ranges from 1.87 mg/L-7.60 mg/L, CO2 ranges from 7.10 mg/L-32.41 mg/L, pH ranges from 5–6, temperatures ranges from 24-32°C, transparency ranges from 101-135 cm, depth ranges from 34-41 m. Two-way Anova test showed that the concentration of DO, CO2, and pH between Tanjung Kudu Lake and Koto Panjang Hydroelectric Reservoir were significantly different.Keywords: Water Quality Parameters, Tanjung Kudu Lake, Koto Panjang Hydroelectric Reservoir